Severe virus associated community acquired pneumonia: predictors of lethality - T. O. Pertseva; T. V. Kireyeva; K. O. Bielosludtseva; S. V. Boltyanskiy; O. P. Nazarenko (Zaporožskij Medicinskij Žurnal)
Despite the fact that the influenza virus pathogenicity factors have been well studied in vitro, in vivo lack is presented in understanding of the those risk factors, objective and laboratory parameters, which related most of all to the fatal virus-associated community-aquired pneumonia (CAP).